2010
DOI: 10.1183/09031936.00050410
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids and the metabolic syndrome in patients with obstructive sleep apnoea

Abstract: Obesity and metabolic syndrome (MS) occur frequently in patients with obstructive sleep apnoea syndrome (OSAS). We hypothesised that circulating free fatty acids (FFAs) are elevated in OSAS patients independently of obesity. This elevation may contribute to the development of MS in these patients.We studied 119 OSAS patients and 119 controls. Participants were recruited and studied at sleep unit of our institution (Hospital Universitari Son Dureta, Palma de Mallorca, Spain) and were matched for sex, age and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 34 publications
2
48
2
Order By: Relevance
“…Finally, sustained adipose tissue hypoxia or activation of hypoxia-regulated signaling pathways can stimulate lipolysis (18,28,29); however, it is worth noting that IH exposure is characterized by distinct cellular and molecular features, which are different from exposure to sustained hypoxia (30,31). Using glycerol release and adipocyte size distribution as functional and morphological indices of adipocyte lipolysis, this study showed that IH exposure stimulated basal lipolysis, thus providing a functional explanation for results seen in previous studies that reported increased plasma FFA levels in patients with OSA and rodents exposed to IH (7,25,32,33). These results demonstrate that lipolysis represents a process regulated by IH exposure in vivo, together with secretion of adipokines or gene expression regulation (4).…”
Section: Discussionsupporting
confidence: 57%
“…Finally, sustained adipose tissue hypoxia or activation of hypoxia-regulated signaling pathways can stimulate lipolysis (18,28,29); however, it is worth noting that IH exposure is characterized by distinct cellular and molecular features, which are different from exposure to sustained hypoxia (30,31). Using glycerol release and adipocyte size distribution as functional and morphological indices of adipocyte lipolysis, this study showed that IH exposure stimulated basal lipolysis, thus providing a functional explanation for results seen in previous studies that reported increased plasma FFA levels in patients with OSA and rodents exposed to IH (7,25,32,33). These results demonstrate that lipolysis represents a process regulated by IH exposure in vivo, together with secretion of adipokines or gene expression regulation (4).…”
Section: Discussionsupporting
confidence: 57%
“…In the study by Barceló et al, in the non-obese population only OSA patients without MetS had higher levels of free fatty acids, as no significant differences were found in biomarkers between OSA and non-OSA in patients with established MetS. 11 Surprisingly, when we reviewed the non-OSA-non-MetS patients, there were no differences in the biomarkers explored. Those patients who supposedly constituted the metabolically healthier group in fact presented lower blood pressure, serum triglyceridemia, and fasting glucose, while their HDL cholesterol was higher, although they already had the same biomarker profile.…”
Section: Discussionmentioning
confidence: 93%
“…To address this issue, Barceló et al excluded patients with obesity and matched a sleep unitreferred cohort by BMI; OSA patients showed higher levels of free fatty acids, CRP, and oxidative stress markers. 11 Trombetta et al matched MetS patients by BMI with and without OSA; they demonstrated that in this high-risk cardiovascular population with moderate obesity, OSA was associated with greater sympathetic drive. 12 Moreover, there have been few casecontrol studies that matched patients by central adiposity to study the effect of OSA on the different components of MetS 13 and the different biomarkers 14 related to both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating FFA have been recently reported in patients with OSA without MetS compared to sex-, age-and BMI-matched controls [222] and in patients with chronic heart failure and OSA during sleep [223], suggesting an effect of OSA on lipid metabolism independent of concurrent obesity.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 96%